Determination of the Efficiency of the Turbogenerator B3 Rated 412 MVA at Thermal Power Plant “Kostolac B” - Klasnić, Ilija G; Dragićević, Miroslav; Joksimović, Dušan; Šarić, Darko; Lazović, Željko (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
In modern power systems, which are rapidly transforming toward a sustainable future, the role of conventional generation units — synchronous generators — remains of fundamental importance. During the ongoing energy transition, the increasing share of renewable energy sources connected to the grid through power electronic converters poses a challenge, as their generation does not inherently contribute to the system’s inertial stability. For this reason, the construction of the new unit B3 at thermal power plant Kostolac B, equipped with a synchronous turbogenerator, has particular significance for the Serbian power system. It ensures the preservation of system reliability and operational security while enabling further integration of renewable energy sources. This paper presents the results of the performance tests of the B3 turbogenerator, rated 412 MVA (350 MW), at thermal power plant Kostolac B, with a focus on determining the generator efficiency — one of the guaranteed parameters defined in the contract between the supplier and the customer. In the context of achieving green agenda objectives, where maximum reliability and optimal utilization of existing resources are required, precise determination of generator efficiency is of great importance. The tests were carried out on-site, following a methodology agreed upon between the supplier and the customer, and in accordance with the IEC 60034 standard for rotating electrical machines. The generator efficiency was determined using the calorimetric method, selected as the reference approach due to its highest accuracy and minimal measurement uncertainty. The obtained results confirm that the achieved efficiency of the B3 turbogenerator exceeds the guaranteed value, thereby validating the high quality of the delivered equipment.